1983
DOI: 10.1523/jneurosci.03-11-02240.1983
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal changes in the firing rate of neostriatal and dorsal raphe neurons following local infusions or systemic injections of D- amphetamine: evidence for neostriatal heterogeneity

Abstract: A local infusion of d-amphetamine (d-AMPH) into the dorsal raphe nucleus (DRN) inhibited neuronal activity in this site and produced a mirror-image excitation in the ventrolateral, but not dorsomedial, neostriatum. This effect, which was mimicked by &methoxy-N,N-dimethyltryptamine, a serotonin autoreceptor agonist, was not altered by pretreatment with cu-methyl-p-tyrosine. Similar regional differences in neostriatal activity were obtained following an electrolytic lesion of the DRN or an intraperitoneal inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…1, Table 1), MP (Fig. 2), APO (Table 2), and amfonelic acid (Waldmeier et al 1983) may reflect stimulant-induced increases in the activity of DRN 5HT neurons, Consistent with this interpretation, Gallagher and Aghajanian (1976) reported that 3 mg/kg AMPH increased the firing rate of DRN neurons, and Rebec and Curtis (1983) have shown that moderate doses of AMPH produce a prolonged increase in activity of cells recorded from the DRN. Further, Geyer and his coworkers have noted that stereotypic doses of AMPH and MP (Geyer et al 1975) and doses of APO above 0.1 mg/kg (Lee and Geyer 1982) alter cytofluorometric measures of cellular 5HT in a manner consistent with enhanced 5HT release and utilization in DRN but not in median raphe.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…1, Table 1), MP (Fig. 2), APO (Table 2), and amfonelic acid (Waldmeier et al 1983) may reflect stimulant-induced increases in the activity of DRN 5HT neurons, Consistent with this interpretation, Gallagher and Aghajanian (1976) reported that 3 mg/kg AMPH increased the firing rate of DRN neurons, and Rebec and Curtis (1983) have shown that moderate doses of AMPH produce a prolonged increase in activity of cells recorded from the DRN. Further, Geyer and his coworkers have noted that stereotypic doses of AMPH and MP (Geyer et al 1975) and doses of APO above 0.1 mg/kg (Lee and Geyer 1982) alter cytofluorometric measures of cellular 5HT in a manner consistent with enhanced 5HT release and utilization in DRN but not in median raphe.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to these high dose effects of AMPH, electrophysiological (Foote et al 1969;Gallagher and Aghajanian 1976; Baraban et al 1978 ;Rebec and Curtis 1983) and cytofluorometric (Geyer et al 1975) data indicate profound effects on apparent 5HT function at moderate doses of AMPH which enhance locomotor activity or promote focused stereotypies. Further, some evidence suggests a role for 5HT in modulating both AMPH-induced locomotor activity (Neill et al 1972;Mabry andCampbell 1973, Breese et al 1974;Costall and Naylor 1974) and stereotypies (Sega11976; Sloviter et al 1978 b;Lucki and Harvey 1979).…”
mentioning
confidence: 96%
“…Serotonergic systems have long been suspected of modulating amphetamineinduced stereotypy (see Segal and Kuczenski 1994) and are known to influence striatal neuronal activity (Rebec and Curtis 1983). Amphetamine-induced interactions between dopamine and serotonin are likely at the neuronal level and should be pursued in future work with behaving animals.…”
Section: Discussionmentioning
confidence: 99%
“…Will et al (1998Will et al ( , 2002 suggested that these results might have been a product of the interaction between the sensitization of DRN neurons selectively produced by IS and dopaminergic (DA) processes in either the nucleus accumbens (NAc) or the medial prefrontal cortex (mPFC). Serotonin in these structures can potentiate DA release (Rasmusson et al, 1994), and it is noteworthy that morphine activates DRN 5-HT neurons (Tao and Auerbach, 1994) but amphetamine does not (Rebec and Curtis, 1983). Given that IS sensitizes DRN 5-HT neurons, morphine might be expected to produce exaggerated extracellular levels of 5-HT in projection regions of the DRN such as the mPFC in subjects that had been previously exposed to IS, thereby potentiating DA levels in them and thus potentiating reward-related processes.…”
Section: Introductionmentioning
confidence: 99%